The Influence of User-Generated Content (UGC) And Store Atmosphere on Purchase Decision - Raida Syafira Azzahra; Safarudin Hisyam Tualeka (Manajemen Multitalenta Indonesia, 2026)
The rapid growth of coffee shop businesses in Indonesia, together with the increasing use of TikTok, has changed how consumers obtain information before making purchase decisions. However, Toko Kopi Jaya Malang presents an interesting case because its growth is not mainly driven by official TikTok promotion, but by organic user-generated content and the distinctive atmosphere offered in its stores. This study aims to examine the influence of User-Generated Content (UGC) and store atmosphere on consumers’ purchase decisions at Toko Kopi Jaya Malang. This research employed a quantitative approach with an explanatory research design. Data were collected from 215 respondents selected through purposive sampling and analyzed using IBM SPSS Statistics 31. The analysis involved classical assumption tests, multiple linear regression, and hypothesis testing. The results showed that UGC significantly influenced purchase decisions, p < .05, and store atmosphere also had a significant influence on purchase decisions, p < .05. Simultaneously, both variables significantly affected purchase decisions, with a coefficient of determination of R² = .637. This indicates that 63.7% of the variation in purchase decisions can be explained by UGC and store atmosphere. The study concludes that digital exposure through UGC and direct physical experience through store atmosphere are important factors in shaping consumer purchase decisions.